KAJIAN ETNOPEDAGOGI TERHADAP NILAI FILOSOFIS RUMAH ADAT TONGKONAN SEBAGAI SUMBER BELAJAR DI SEKOLAH DASAR - Lutma Ranta Allolinggi; Ady Akbar; Titik Pitriani Muslimin; Sitti Hasnah; Sayidiman (STKIP Subang, 2026)
This study aimed to explore the philosophical values embedded in the carvings of the Tongkonan Traditional House and analyze their potential as learning resources for elementary schools. A descriptive qualitative approach was employed, utilizing document analysis and semi-structured interviews with Torajan cultural experts selected through purposive sampling. The data were analyzed using thematic analysis involving data reduction, theme categorization, interpretation, and conclusion drawing. The findings revealed that the carvings Pa' Barre Allo, Pa' Tedong, Pa' Londongan, Pa' Sussuk, and Pa' Don Bolu embody philosophical values of religiosity, gratitude, hard work, responsibility, leadership, mutual cooperation, unity, and tolerance. These values are relevant for integration into various elementary school subjects, including Pancasila Education, Science and Social Studies (IPAS), Religious Education, Indonesian Language, and Visual Arts. Furthermore, the findings indicate that Tongkonan carvings have strong potential as ethnopedagogical learning resources that foster character development, critical thinking, creativity, and problem-solving skills. Therefore, the philosophical values embedded in Tongkonan carvings can be utilized to promote meaningful learning while simultaneously preserving Torajan cultural heritage